2015
DOI: 10.1097/mao.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Can Nasal Decongestants Improve Eustachian Tube Function?

Abstract: Our acute studies revealed no improvement in eustachian ventilatory tube function with the administration of nasal decongestants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…evaluated the effects of intratympanic and nasal applications of xylometazoline 0.1 per cent on Eustachian tube opening, using pressure equalisation tests and tubomanometry. 7 Their results showed that nasal or intratympanic use of the decongestant had little to no effect on Eustachian tube opening. van Heerbeek et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…evaluated the effects of intratympanic and nasal applications of xylometazoline 0.1 per cent on Eustachian tube opening, using pressure equalisation tests and tubomanometry. 7 Their results showed that nasal or intratympanic use of the decongestant had little to no effect on Eustachian tube opening. van Heerbeek et al .…”
Section: Discussionmentioning
confidence: 99%
“…18 The fact that a measurable change in Eustachian tube opening was registered suggests that the decongestant spray reached the pharyngeal opening of the Eustachian tube, which is something that has been questioned previously in the literature. 7,9 However, a change in Eustachian tube opening was only seen in one aspect of several tests applied, providing insufficient evidence on which to base this conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. oral verabreichtes Phenylephrin [21,53]. Nasal applizierte abschwellende Medikamente sind zur Akuttherapie von Tubenventilationsstörungen wahrscheinlich wenig oder gar nicht wirksam [21,53,84], werden aber bei anfälligen Personen in der Praxis dennoch oft präventiv eingesetzt. Chirurgische Maßnahmen am Trommelfell (Parazentese, Einlage eines Paukenröhrchens) sind bei PEU äußerst zurückhaltend anzuwenden, da auch kleine Defekte des Trommelfells zu einem Hörverlust führen können [71,94].…”
Section: Obstruktive Tubenventilationsstörungunclassified